Protective Effect of Uric Acid on ox-LDL-Induced HUVECs Injury via Keap1-Nrf2-ARE Pathway - Yajuan Lin; Yunpeng Xie; Zhujing Hao; Hailian Bi; Yang Liu; Xiaolei Yang; Yunlong Xia (Journal of Immunology Research)
Uric acid is an effective antioxidant. Oxidized low-density lipoprotein (ox-LDL) is derived from circulating LDL and promotes atherosclerosis. The Keap1-Nrf2-ARE pathway is a key body pathway involved in protection against internal and external oxidative damages. The role of uric acid on vascular endothelial function damaged by ox-LDL, and its effect on the Keap1-Nrf2-ARE pathway has not been fully explored. HUVECs were treated with different concentrations of uric acid and ox-LDL to explore the effect of uric acid in vitro. Cell phenotype was determined by cytometry and Western blot. Nuclear translocation of Nrf2 was determined by immunofluorescence. Coimmunoprecipitation was used to determine the level of Nrf2 ubiquitination. A microfluidic device was used to mimic the vascular environment in the body, and the level of mRNA levels of inflammatory factors was determined by RT-PCR. The findings of this study show that suitable uric acid can significantly reduce endothelial damage caused by ox-LDL, such as oxidative stress, inflammation, and increased adhesion. In addition, uric acid reduced Nrf2 ubiquitination and increased nuclear translocation of Nrf2 protein, thus activating the Keap1-Nrf2-ARE pathway and playing a protective role. Interestingly, the effects of UA were significantly inhibited by administration of Brusatol, an inhibitor of Nrf2. In summary, suitable concentrations of uric acid can alleviate the oxidative stress level of endothelial cells through Nrf2 nuclear translocation and further protect cells from damage.